Excel-Based Business Analysis Forecasting Key Business Trends - Anari, Ali.; Kolari, James W.; SpringerLink (Online service) (New York, NY : Springer New York, 2012)
No text!
Keywords: Economics; Economics/Management Science; Business/Management Science, general